Practical Aspects of Valuations for Mergers and Divisions - Turcaș, Florin; Dumiter, Florin; Brezeanu, Petre; Fărcaș, Pavel (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The purpose of this article is to present the main problems posed by mergers and divisions, to valuators and experts, called to certify their correctness. This material summarizes the main Romanian and European legislative norms in the field, and shows, through a series of practical examples, which should be the internal legislative changes, in order to avoid logical contradictions, that may arise. This paper proposes a number of solutions and invites professionals and corporations to contribute to legislative regulation of reported issues.